PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE PERUSAHAAN DAN PROFITABILITAS TERHADAP RETURN SAHAM: STUDI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Fitri, Raisa (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
This research aimed to analyze the influence the dividend policy proxied by Dividend Payout Ratio (DPR), leverage the company proxied by Debt to Equity Ratio (DER) and profitability proxied by Return On Equity (ROE) to return stock in companies manufacturing sub-sectors of the food and drinks listed in Indonesia Stock Exchange period 20013-2015. This study uses quantitative methods. The sampling technique used purposive sampling method and selected according to established criteria. Model analysis used multiple linear regression. From the analysis of the following results, dividend policy (DPR), the company's leverage (DER), profitability (ROE) either partially or simultaneously has no effect on stock returns